FEATURES OF LIFE OF URBAN ENVIRONMENT MEDITERRANEAN (ILLUSTRATED OF PATRAS) - , В. А. (Municipal economy of cities (Technical science), 2013)
The specific features of vital functions of city environment are examined with the exposure of negative tendencies (t. Patra).